PENYULUHAN TINDAK PIDANA CYBER BULLYING BERDASARKAN UNDANG –UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Rian Prayudi Saputra (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Internet access has become a habit for most people. Another interesting social networking site has also become the choice of media enthusiasts, one of which is the Facebook social network. The existence of Facebook certainly has positive and negative impacts. One of the negative effects of using Facebook is using it as a tool for Internet harassment. Cyberbullying often occurs among teenagers. Several things are due to environmental influences, school fights, imitation in the use of Facebook have an impact on the occurrence of cyberbullying, people who are bullied online do not understand the impact of using Facebook social networks, lack of attention from parents and teachers, victims of bullying Cyberbullying like to talk about it with friends and kept it to himself, and eventually cyberbullying ensued.